Situation awareness in the speech therapy domain: A systematic mapping study. (January 2019) - Franciscatto, Maria Helena; Augustin, Iara; Lima, João Carlos Damasceno; Maran, Vinícius
Highlights: We present an overview of the SA integration in the speech therapy domain, showing criteria that are consolidated. we survey the most used methods along with descriptions of where each one is commonly applied. We address the projection capability of each study selected, for evaluating how decision-making is presented in the domain. We demonstrate how SA integration has evolved over time, comparing criteria evaluated in this paper and in previous work. We provide directions for further research, pointing out challenges and opportunities in the speech therapy domain. Abstract: Situation Awareness (SA) involves the correct interpretation of a situation, allowing a system to respond to the observed environment and providing support for decision making in many systems domains. Speech therapy is an example of domain where situation awareness can provide benefits, since practitioners should monitor the patient in order to perform therapeutic actions. However, there are a few studies in the area that address reasoning about a situation to improve these tasks. For this reason, this systematic mapping study aims to identify and compare different proposals in the speech therapy domain in order to verify which aspects related to obtaining and maintaining SA are supported. Our analyzes provide useful insights on whats aspects of SA are best integrated in the speech domain - such as knowledge bases and adaptation - and other aspects that remain to be improved - like the action support and projection abilities. Also, this paper includes statistics, methodologies used by different authors and other issues involving research processes. As main contributions, this work presents an overview of the SA integration in the speech therapy domain, discussing challenges in the area and providing directions for further research.